Presumed Pediatric Isolated Oculomotor Nerve Schwannoma - A Case Report - Boqaaiya S; Raed A; Vidan A; Beiruti Wiegler K; Cohen Y; Chassid O (International Medical Case Reports Journal)
Shadi Boqaaiya,1 Aman Raed,1,2 Aviv Vidan,1,2 Karine Beiruti Wiegler,3 Yuval Cohen,1,2 Otzem Chassid1,2 1Ziv Medical Center; Department of Ophthalmology, Safed, 1311001, Israel; 2Azrieli Faculty of Medicine, Bar-Ilan University, Safed, 1311502, Israel; 3Research Wing, Ziv Medical Centre, Safed, 1311001, IsraelCorrespondence: Otzem Chassid, Department of Ophthalmology, Ziv Medical Center, Harambam Street 1, Safed, 1311001, Israel, Tel +972 506266059, Email otzemc@ziv.gov.ilAbstract: This report presents a healthy 2.5-year-old child exhibiting headache, ptosis, exotropia, and left mydriasis. Initial neuroimaging, including computed tomography (CT), computed tomography angiography (CTA), and standardized magnetic resonance imaging (MRI), failed to identify any lesions; however, high-resolution MRI revealed an ovoid mass adjacent to the left proximal oculomotor nerve within the superior cavernous sinus. This case underscores the necessity for advanced imaging techniques and a thorough diagnostic approach to enhance understanding of this rare pediatric condition. Moreover, it highlights the limited documentation of pediatric oculomotor schwannomas, leading to an inadequate understanding of their diagnosis and management, and emphasizes the need for enhanced awareness and research to establish effective diagnostic protocols, particularly utilizing advanced neuroimaging techniques.Keywords: headache, peri-tumoral edema, third nerve palsy, high-resolution MRI, steroids